Thanksgiving - Alden, Laura, 1955-; Lexa-Senning, Susan (Chicago : Childrens Press, 1993)
Andrew, Abigail, and Elizabeth help prepare for their Thanksgiving dinner, share the story of the first Thanksgiving, and name the things for which they are thankful. Includes crafts, games, and activities.
2.3
K-3
Keywords: Thanksgiving Day -- Fiction; Thanksgiving Day -- Fiction